Clinical analysis of lectin-like oxidized low-density lipoprotein receptor-1 in patients with in-stent restenosis after percutaneous coronary intervention. Issue 17 (April 2018) - Liu, Junfeng; Liu, Yunde; Jia, Kegang; Huo, Zhixiao; Huo, Qianyu; Liu, Zhili; Li, Yongshu; Han, Xuejing; Wang, Rong
Abstract : Abstract: In-stent restenosis (ISR) is the most common complication associated with percutaneous coronary intervention (PCI). Although some studies have reported an association between lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) and ISR, not enough clinical validation data are available to support this link. Here, we report our cross-sectional study aimed at exploring the feasibility of LOX-1 as a biomarker for the prognostic diagnosis of patients undergoing PCI. Three groups were included: ISR group, including 99 patients with ISR diagnosed with coronary arteriography (CAG) after PCI; lesion group, comprising 87 patients with coronary artery stenosis (<50%) diagnosed with CAG after PCI; and control group, consisting of 96 volunteers with no coronary artery disease. The levels of LOX-1 were measured in each patient by using an enzyme-linked immunosorbent assay, and their general information as well as laboratory parameters were recorded and followed up during a period of 2 years. LOX-1 levels gradually increased after PCI along with the progression of the lesion in the 3 groups. The levels of LOX-1 were significantly higher in the ISR group than in the other 2 groups ( P  < .001). LOX-1 levels were correlated with the levels of uric acid (UA) (r = 0.289, P  = .007), creatinine (CREA) (r = .316, P  = .003), and high-density lipoprotein cholesterol (HDL-C) (r = −0.271, P  = .012), whereas no statistically significant correlation was detected with the Gensini score (r = 0.157, P  = .141). The sensitivity and specificity of LOX-1 were 81.5% and 55.7%, respectively, with the most optimal threshold (5.04 μg/L). The area under curve (AUC) of the receiver operator characteristic (ROC) curve of LOX-1 was 0.720, and LOX-1 had the highest AUC compared with CREA, UA, and HDL-C, both individually and in combination. A high level of LOX-1 in the early period after PCI has a certain predictive power and diagnostic value for ISR. However, the level of LOX-1 is not related to the Gensini score of coronary artery after PCI, and CREA and UA, which are weakly related to LOX-1, have no obvious synergy in the diagnosis of ISR with LOX-1. Abstract : Supplemental Digital Content is available in the text